APPROACHING SELF-TRANSLATION IN LATIN AMERICAN INDIGENOUS LITERATURES. THE MAPUCHE BILINGUAL POETRY OF ELICURA CHIHUAILAF AND LILIANA ANCALAO. - Stocco, Melisa (Hispanófila)
The article presents a study which aims at the issue of self-translation in contemporary Indigenous literatures from the perspective of the ‘spatial turn' and concept of ‘ch'ixi' developed by Silvia Rivera Cusicanqui. It mentions that Ch'ixi is a notion that contrasts with the idea of ‘hybridity that the cultural scenario of Indigenous latin America "manifests an active recombination of opposed worlds and contradictory meanings.